Process evaluation of a co-designed best practice model of dementia care in Aboriginal and Torres Strait Islander primary care: The Let's CHAT (Community Health Approaches To) Dementia project - Kate Bradley; Jo-anne Hughson; Irene Blackberry; Lauren Poulos; Kylie Sullivan; Naomi Paine; Roslyn Malay; Diane Cadet-James; Harold Douglas; Bridget Allen; Bonnie Martin-Giles; Kate Fulford; et al. (SSM - Mental Health)
Optimising brain health for older Aboriginal and Torres Strait Islander peoples is important given the high rates of cognitive impairment and dementia (CI/D) in this population. To achieve this, effective models of care for the primary care setting are needed. This paper reports on the process evaluation of a stepped-wedge cluster randomised controlled trial conducted with 12 Aboriginal Community Controlled Health Services (ACCHSs) across four states of Australia. The study implemented a culturally responsive, co-designed best-practice model of CI/D care for Aboriginal and Torres Strait Islander peoples. Utilising the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) Framework, the process evaluation aimed to identify the components of a “successful implementation” for this type of intervention. Qualitative and quantitative data collected included interviews, workshop evaluation forms, implementation checklists, and researcher observational notes. Fidelity to the intervention (scored as low, medium or high) was medium overall. Dose delivered across ACCHSs and intervention activities varied markedly. The project's reach was high and ACCHS staff demonstrated high engagement. Major themes derived from the qualitative data were: 1. ‘Aboriginal health and diverse environmental ecosystems’; 2. ‘Reciprocal relationships built on collaboration and cultural responsiveness’; 3. ‘Community knowledges and understandings of memory and thinking problems’. Despite encountering several challenges, the intervention improved management of dementia, and had high uptake and acceptability among ACCHS staff. Identified factors affecting the intervention, notably related to context, will inform future initiatives to improve dementia care in primary care settings.